Increased sodium fluorescein transport by corticosteroids is inhibited by a LAT-1 specific inhibitor in retinal pigment epithelial cells in vitro - Norihiko Misawa; Shigeru Honda (Scientific Reports, 2023)
Abstract To investigate whether aldosterone (ALD) and hydrocortisone (HC) change the gene expression of SLC7A5, which encodes the large neutral amino acid transporter small subunit 1 (LAT1), and the transport activity of LAT1 in the retinal pigment epithelium (RPE) in vitro. ARPE-19 cells were grown to confluence. After withdrawing the serum, ALD or HC was added with several doses and incubated, and SLC7A5 gene expression was measured. The influx and efflux transport of sodium fluorescein (Na-F) were evaluated using the Transwell culture system. SLC7A5 gene expression was upregulated by ALD and downregulated by HC in a dose-dependent manner. Both ALD and HC significantly increased the influx and efflux Na-F transport of RPE cells at a dose that did not change the expression of SLC7A5. JPH203, a specific inhibitor of LAT1, significantly reduced accelerated Na-F transport. Both ALD and HC increased the gene expression of zonula occludin-1 (ZO-1) although they did not change the immunoreactivity of ZO-1 in RPE cells. LAT1 may play an important role in increasing Na-F transport associated with ALD and HC administration. A specific LAT1 inhibitor may effectively regulate the increased material transport of RPE induced by ALD and HC.